2016
DOI: 10.1111/mec.13741
|View full text |Cite
|
Sign up to set email alerts
|

Midgut fungal and bacterial microbiota of Aedes triseriatus and Aedes japonicus shift in response to La Crosse virus infection

Abstract: Understanding how midgut microbial communities of field-collected mosquitoes interact with pathogens is critical for controlling vector infection and disease. We used 16S rRNA and internal transcribed spacer sequencing to characterize the midgut bacterial and fungal communities of adult females of Aedes triseriatus and Aedes japonicus collected as pupae in tree holes, plastic bins and waste tires and their response to La Crosse virus (LACV) infection. For both mosquito species and across all habitat and virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 80 publications
8
68
0
4
Order By: Relevance
“…Similar individual variability in gut microbiota and the dominance of a few bacterial taxa in mosquito guts has been reported before [22]. These variations may result from individual variations in external and internal factors such as the gut physiological conditions, larval and adult diet, infection with parasites and pathogens, host aging [24, 26, 27, 38, 42], and host genetic background [43]. Our experimental design cannot decipher the contribution of these factors to the observed pattern of gut microbiota since adult mosquito samples were collected using the CDC light traps and we had no prior knowledge of the factors these mosquitoes were exposed to before collection.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar individual variability in gut microbiota and the dominance of a few bacterial taxa in mosquito guts has been reported before [22]. These variations may result from individual variations in external and internal factors such as the gut physiological conditions, larval and adult diet, infection with parasites and pathogens, host aging [24, 26, 27, 38, 42], and host genetic background [43]. Our experimental design cannot decipher the contribution of these factors to the observed pattern of gut microbiota since adult mosquito samples were collected using the CDC light traps and we had no prior knowledge of the factors these mosquitoes were exposed to before collection.…”
Section: Discussionsupporting
confidence: 56%
“…These studies have revealed that the composition and diversity of gut microbiota can vary dramatically within [22] and between mosquito species [23] and are influenced by host diet [24], developmental stage [24], larval environment [25], and pathogen infection [26, 27]. As such, additional studies comparing the microbial communities of different mosquito species can further improve our understanding of mosquito microbiota and propel identification of specific microbes that may be harnessed for disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Several bacteria identified as gut community members in mosquitoes have also been isolated and successfully cultured [13, 18, 22, 31, 5053]. Unicellular eukaryotes identified as gut community members in different species of mosquitoes include fungi, algae, and Apicomplexa but thus far none of these organisms have been isolated from mosquitoes and cultured independently [43, 48, 5457]. Sequence-based surveys also identify a number of viruses in mosquitoes [58, 59].…”
Section: Composition Of the Gut Microbiotamentioning
confidence: 99%
“…A large number of studies indicate that bacterial diversity differs substantially both between and within mosquito species as a function of collection location and other factors [1418, 30, 4246, 62, 63]. On a local scale, factors implicated in affecting community composition include habitat preferences of different mosquito species and larval feeding behavior [18, 30, 62].…”
Section: Composition Of the Gut Microbiotamentioning
confidence: 99%
“…Recent improvements in the exploration of microscopic organisms through the use of metagenomic PCR (Hugenholtz, Goebel, & Pace, 1998; Liles, Manske, Bintrim, Handelsman, & Goodman, 2003) and next‐generation sequencing (Logares et al., 2012) have allowed more accurate and sensitive documentation of these organisms. Several studies have characterized and compared mosquito bacterial microbiota in natural habitats (Akorli et al., 2016; Buck et al., 2016; Gimonneau et al., 2014; Minard et al., 2012, 2014, 2015; Tchioffo et al., 2015; Yadav et al., 2015; Zouache et al., 2010) but few have characterized eukaryotes and in such cases have targeted fungi (Muturi, Bara, Rooney, & Hansen, 2016; Muturi, Ramirez, Rooney, & Dunlap, 2016; Steyn, Roets, & Botha, 2016). We document mosquito microbiota composition and diversity for vector species Aedes aegypti , Aedes albopictus , and Culex quinquefasciatus across ecologically distinct, yet geographically proximate, habitats in Thailand where many mosquito‐borne diseases circulate.…”
Section: Introductionmentioning
confidence: 99%